KUALITAS KIMIA DAGING KERBAU KALIMANTAN SELATAN (Buballus bubalis) PADA EKOSISTEM PEMELIHARAAN BERBEDA - Habibah Habibah; Tanwirul Millati; Intan Aulia (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
This study aims to determine the chemical quality (water content, protein content and fat content) of South Kalimantan swamp buffalo meat in different ecosystems. The research was conducted using survey and laboratory methods. Meat samples were taken from three Slaughterhouses (RPH), RPH Basirih, RPH Martapura and RPH Pelaihari. The samples were then taken to the laboratory to test the chemical quality of buffalo meat. The sample of swamp buffalo meat used was the Longissimus dorsi muscle. The resulting data were analyzed and tabulated based on the maintenance ecosystem, namely the swamp buffalo kept in the swamp ecosystem and the swamp buffalo kept in the terrestrial ecosystem. The data obtained were then grouped and tested using the Independent Samples Test. The results showed that the difference in the buffalo rearing ecosystem did not affect the protein and fat content but had a very significant effect on the water content of the buffalo meat produced (P<0.01).